2021
DOI: 10.1152/ajpendo.00473.2020
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of human adipocytes identifies depot-specific heterogeneity at metabolic control points

Abstract: Adipose tissue is a primary regulator of energy balance and metabolism. The distribution of adipose tissue depots is of clinical interest because the accumulation of upper-body subcutaneous (ASAT) and visceral adipose tissue (VAT) is associated with cardiometabolic diseases, whereas lower-body gluteal-femoral adipose tissue (GFAT) appears to be protective. There is heterogeneity in morphology and metabolism of adipocytes obtained from different regions of the body, but detailed knowledge of the constituent pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 76 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have characterized the proteome of isolated human adipocytes and found massive depot-specific differences ( 43 , 44 ). However, the context of adipocytes in their native environment and the interplay with other cell types is crucial to understand the state of adipose tissue in health and disease.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have characterized the proteome of isolated human adipocytes and found massive depot-specific differences ( 43 , 44 ). However, the context of adipocytes in their native environment and the interplay with other cell types is crucial to understand the state of adipose tissue in health and disease.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity of adipose tissue is driven by differences in sex, genetics and environment, but also by the various depots existing in humans and their cellular composition [57]. It is well known that diversity in morphology, metabolism and function shapes metabolic status, negatively influencing the entire energy balance and controlling the appearance of metabolic diseases [58]. On the other hand, the dynamic interactions of the SVF cells with the milieu through paracrine and endocrine signaling can positively impact the local and systemic responses stimulating anti-inflammatory and proangiogenic activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue plays a central role in energy homeostasis and metabolic function [reviewed in (2,53)], and its development and functions are regulated by insulin signaling (54). Metabolic and functional characteristics differ between adipose tissue depots and their specific contribution to metabolic health and disease is extensively studied (9,14,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%